FORMATION OF HEALTHCARE COMPETENCE OF PRIMARY SCHOOL STUDENTS IN STUDYING THE INTEGRATED COURSE «I AM EXPLORING THE WORLD» - Samoilenko, О.; Bilousova, N.; Yarosh, O. (Видавництво НДУ, 2021)
The article is devoted to the research of the problem of formation of healthcare competence of junior high school students in studying the integrated course «I am exploring the world». An analysis of the psychological and pedagogical literature on the preservation of human health has led to the conclusion that life priorities are formed primarily in the educational institution. Therefore, the future of the child and the country as a whole depends on what they will be like. The article finds that the positive pedagogical effect in the formation of healthcare competence of junior high school students in the educational process in the study of integrated courses, including «I am exploring the world», gives compliance with the following pedagogical conditions: implementation of axiological approach to junior high school students healthcare competence; stimulating the active role position of students in the process of mastering health skills; organizational and methodological support of proper support in the formation of skills of healthcare competence. The article proves that integrated disciplines help to expand of junior high school students understanding of the environment in which they live, the relationship of phenomena and objects, mutual assistance, the existence of a diverse world of material and artistic culture. Hence, the use of modern forms, methods, techniques, tools and methods of organizing lessons, including the integrated course «I am exploring the world», which is important in health, health, promoting the health of young students. At the same time, it helps the teacher to solve the main tasks in the educational institution: improving the quality of education, the formation of health competence in junior high school students and comprehensive education of the individual.
Keywords: healthcare competence; primary school students; pedagogical conditions